Chemodivergent transformations of amides using gem-diborylalkanes as pro-nucleophiles - Wei Sun (Nature Portfolio, 2020)
Amides are versatile synthetic building blocks, however the general stability of the amide bond makes its selective transformation challenging. Here, the authors report a chemodivergent transformation of primary, secondary and tertiary amides by using 1,1-diborylalkanes as pro-nucleophiles.